ANALYSIS OF CONSUMERS' ATTITUDES TOWARDS THE SUSTAINABLE DEVELOPMENT OF THE TOURISM SECTOR IN THE LITHUANIA REGIONS - Narkūnienė, Ramutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the article, the author analyzes the attitude of consumers towards the sustainable development of the tourism sector in the Lithuania regions. The purpose of the research is to analyze the attitude of consumers towards the sustainable development of the tourism sector in the Lithuania regions. During the research, a quantitative survey (questionnaire survey) was conducted. Data collection methods - analysis of scientific literature and sources, document analysis, questionnaire survey. The article analyzes the consumers' attitude towards the sustainable development of the tourism sector from a theoretical point of view and presents the results of the conducted research. It is concluded that the respondents consider the following factors of sustainable development of the tourism sector to be the most important: development of ecological tourism; accessibility of tourism; creation of tourist routes accessible to all; certification of tourism services; development of the common national route and development of bicycle tourism infrastructure, etc. According to the respondents, the following problems of sustainable development of the tourism sector are usually encountered: economic problem: insufficient investments in the development of sustainable tourism; lack of knowledge about the essence and principles of sustainable tourism in local politics; underdeveloped tourism sector infrastructure, etc.